2007
DOI: 10.3168/jds.2007-0066
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Lipid Metabolism in Transition Dairy Cows Fed Flaxseed

Abstract: Thirty-three Holstein cows averaging 687 kg of body weight were allotted 6 wk before the expected date of parturition to 11 groups of 3 cows blocked within parity for similar calving dates to determine the effects of feeding different sources of fatty acids on blood parameters related to fatty liver and profile of fatty acids in plasma and liver. Cows were fed lipid supplements from 6 wk before the expected date of parturition until d 28 of lactation. Cows within each block were assigned to 1 of 3 isonitrogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
45
4
16

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 35 publications
17
45
4
16
Order By: Relevance
“…In addition, cows fed diets containing WS and CSFA (n-6 FA sources) exhibited higher C18:1 trans-11 and C18:2 in milk fat than WF, which are related to human health benefits (Lock and Bauman, 2004). These results are similar to those previously cited in literature (Petit et al, 2007;Zachut et al, 2010), which reported higher concentration of C18:2 FA when cows were fed WS and CSFA. When a FA source is added to ruminant diets, most of the FA can be modified through the biohydrogenation process, which is usually not completed resulting in a wide variety of FA.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, cows fed diets containing WS and CSFA (n-6 FA sources) exhibited higher C18:1 trans-11 and C18:2 in milk fat than WF, which are related to human health benefits (Lock and Bauman, 2004). These results are similar to those previously cited in literature (Petit et al, 2007;Zachut et al, 2010), which reported higher concentration of C18:2 FA when cows were fed WS and CSFA. When a FA source is added to ruminant diets, most of the FA can be modified through the biohydrogenation process, which is usually not completed resulting in a wide variety of FA.…”
Section: Discussionsupporting
confidence: 82%
“…In the first experiment, feeding diets of whole flaxseed had no effect on prepartum dry matter intake (5.2 to 5.9% flaxseed in the dry matter) but increased postpartum intake (10.8 to 12.0% flaxseed in the dry matter) of cows by 9% compared with diets containing 4.9 to 5.2% calcium salts of palm oil or 14.0 to 15.4% micronized soybeans (Petit and Benchaar 2007). In the second experiment, feeding diets of whole flaxseed had no effect on feed intake during the transition period (from week 6 prepartum to week 4 postpartum); however, multiparous cows fed postpartum diets of 11% whole flaxseed compared with those fed a control diet with no added fat or a diet of 3.5% saturated and rumen inert fat sources had the highest and lowest liver concentrations of glycogen and triglycerides, respectively (Petit et al 2007a). These results suggest that flaxseed supplementation may prevent the development of fatty liver in the transition dairy cow.…”
Section: Feed Intake and Digestibilitymentioning
confidence: 95%
“…Feeding diets of whole flaxseed at around 11.8% of the dry matter resulted in similar milk somatic cell score (log 10 SCC) compared with diets of sunflower seeds in the mid stage of lactation and to diets of calcium salts of soybean oil (Cavalieri et al 2005) or calcium salts of palm oil and micronized soybeans in the early stage of lactation (Petit and Benchaar 2007). However, feeding diets of 10% whole flaxseed compared with energy booster, a saturated fat (Petit et al 2007a) or compared with diets with no fat (Petit et al 2007b) decreased milk SCC of dairy cows in the early stage of lactation. There is some evidence that feeding plant oil rich in omega-3 fatty acids alters the production of cytokines and the functional properties of macrophages, lymphocytes, and other immunocompetent cells as shown a reduced proliferative response of activated peripheral blood mononuclear cells of dairy cows fed whole flaxseed (Lessard et al 2003), which could help to maintain integrity of the embryo.…”
Section: Somatic Cell Countmentioning
confidence: 99%
“…Liver condition was better in cows supplemented with full-fat soy than in those fed hydrolyzed palm oil (Bellová et al, 2009). Hepatic lipid accumulation even decreased in transition dairy cows (Petit et al, 2007), when the source of dietary fat was rich in alpha-linolenic acid (18:3 n-3), for example linseed. In dairy goats, linseed has been extensively used to improve the milk FA profile, but to our knowledge its impact on hepatic and kidney metabolism has not been evaluated.…”
Section: Introductionmentioning
confidence: 96%